2007
DOI: 10.1037/0022-006x.75.1.72
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of goal choice interventions for alcohol use disorders among men who have sex with men.

Abstract: This study tested the efficacy of behavioral treatments for alcohol use disorders (AUD) among men who have sex with men (MSM) and who are at risk for HIV transmission. HIV-negative MSM with current AUD (N = 198) were recruited, offered treatment focused on reducing drinking and HIV risk, and followed during treatment and 12 months posttreatment. Participants (n = 89) accepted treatment and were randomized to either 4 sessions of motivational interviewing (MI) or 12 sessions of combined MI and coping skills tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(144 citation statements)
references
References 39 publications
7
135
0
2
Order By: Relevance
“…Implicit in MI, as in most psychosocial models of behavior change, is the assumption that risk behaviors are largely under the control of the individual (Fisher & Fisher, 2000), and the intervention therefore risks failing to address the full range of factors that influences MSM's sexual behaviors, such as the strong interpersonal and social forces (see, e.g., Berg, 2008;Muñoz-Laboy & Dodge, 2007;Tieu et al, 2011). Among the three included studies in this systematic review that assessed the effectiveness of MI on both AOD use and sexual risk behaviors, two found an effect for AOD use but not sexual risk behaviors (Morgenstern et al, 2007;Velasquez et al, 2009), and the third found no effect for either outcome type (Morgenstern et al, 2009). Also previous efforts to reduce sexual risk behaviors using MI have yielded mixed results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implicit in MI, as in most psychosocial models of behavior change, is the assumption that risk behaviors are largely under the control of the individual (Fisher & Fisher, 2000), and the intervention therefore risks failing to address the full range of factors that influences MSM's sexual behaviors, such as the strong interpersonal and social forces (see, e.g., Berg, 2008;Muñoz-Laboy & Dodge, 2007;Tieu et al, 2011). Among the three included studies in this systematic review that assessed the effectiveness of MI on both AOD use and sexual risk behaviors, two found an effect for AOD use but not sexual risk behaviors (Morgenstern et al, 2007;Velasquez et al, 2009), and the third found no effect for either outcome type (Morgenstern et al, 2009). Also previous efforts to reduce sexual risk behaviors using MI have yielded mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Authors who failed to reply were sent two follow-up e-mails. Of those contacted, four authors or their colleagues provided the requested information (EXPLORE Study Team, 2004;Morgenstern et al, 2007;van Kesteren et al, 2007;Velasquez et al, 2009).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…26 HIV prevention interventions for MSM may benefit from incorporating screening and=or treatment for alcohol use or depression, thus allowing some MSM to respond more effectively to behavioral change approaches to HIV prevention. 27 With respect to contextual variables, risk reducers were less likely to have met sex partners in the prior 12 months at public cruising areas and via the Internet. This finding is consistent with prior research showing that MSM frequenting specific gay venues are more likely to engage in high risk sexual behaviors 28,29 and more often use substances during sex 30,31 compared to those who do not.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically focused authors have suggested that LGBT clients may feel less supported by staff and clients while in treatment than do heterosexual clients and feel a lack of connection to the treatment program (Cheng 2003;Drabble and Underhill 2002;Finnegan and McNally 2002;Hicks 2000;Kominars and Kominars 1996;Neisen 1997;SAMHSA 2001). Only a few studies, however, have examined what factors may improve treatment for LGBT clients (Driscoll 1982;Morgenstern et al 2007;Paul et al 1996;Senreich 2009bSenreich , 2010Shoptaw et al 2005).…”
Section: Introductionmentioning
confidence: 97%